Using Mobility to Enhance the Routing Process in the MIS System - Kamal, Oudidi; Ahmed, Habbani; Mohammed, Elkoutbi (International Journal of Interactive Mobile Technologies (iJIM), 2009)
In this paper, we introduce the original Mobile Intelligent System (MIS) in embedded FPGA architecture. This node will allow the construction of autonomous mobile network units which can move in unknowns, inaccessible or hostile environnement for human being, in order to collect data by various sensors and transmits them by routing to a unit of distant process. In the sake of improving the performance of routing unit, we propose a measure of mobility. Each node measure its own mobility in the network, based on the change of the links state in his neighboring. This measure of mobility has no unit, and it is calculated by quantification in regular time intervals.